2018
DOI: 10.4314/ahs.v18i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Peer pressure and home environment as predictors of disruptive and risky sexual behaviours of secondary school adolescents

Abstract: BackgroundNot much is understood about the predictive power of home environment and peer pressure on disruptive behaviour and risky sexual behaviour of adolescents.ObjectivesThe study investigated the predictive power of home environment and peer pressure on disruptive behaviour and risky sexual behaviour of adolescents in secondary school class two in Enugu State, Nigeria. Four research questions and four null hypotheses guided the study.MethodsThe design was a cross sectional survey of correlational study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…This study implied that other factors may compel adolescents to indulge in sexual intercourse or not. The disparity in this study and that of [20] could be attributed to multivariate analsysis as the present study adopted a univariate analysis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This study implied that other factors may compel adolescents to indulge in sexual intercourse or not. The disparity in this study and that of [20] could be attributed to multivariate analsysis as the present study adopted a univariate analysis.…”
Section: Discussionmentioning
confidence: 95%
“…On the contrary, [7] also identified that peer influence in adolescence could lead to pro-social as well as antisocial behaviour. Also the study carried out by [20] on peer pressure and home environment as predictors of disruptive and risky sexual behaviour of secondary school adolescents, showed that adolescents who show a heightened sensitivity to positive peer pressure demonstrated lowered risky sexual behaviours while, those with negative peer pressure strongly exhibit disruptive and risky sexual behaviours. This study implied that other factors may compel adolescents to indulge in sexual intercourse or not.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 The home environment refers to aspects of peoples' domestic lives that comprise their living conditions. 20 These factors, such as the residential location, income, parents' education, or marital status, are associated with children's health behaviors. 21,22 Survivors who experience the benefits of family support and peer support may develop a sense of personal control and self-efficacy, which may help overcome some of the barriers to positive health behaviors.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Home environments and social support (family support and peer support) become particularly important in the transition from a period of intensive treatment to everyday life for CCSs and shape their health behaviors 18,19 . The home environment refers to aspects of peoples’ domestic lives that comprise their living conditions 20 . These factors, such as the residential location, income, parents’ education, or marital status, are associated with children’s health behaviors 21,22 .…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Kenyan researchers on the other hand2 report on sexual experiences of 200 secondary school students in Nakuru, where a large number had had sexual experiences. The work by Adimora3 and others, on the other hand, brings to the fore the predictive power of the home environment and peer pressure on disruptive and risky sexual behaviour of adolescents.…”
mentioning
confidence: 99%